Awareness shaping or shaped by prediction and postdiction - Takahiro Kawabe (Frontiers Research Topics, 2015)
We intuitively believe that we are aware of the external world as it is. Unfortunately, this is not entirely true. In fact, the capacity of our sensory system is too small to veridically perceive the world. To overcome this problem, the sensory system has to spatiotemporally integrate neural signals in order to interpret the external world. However, the spatiotemporal integration involves severe neural latencies. How does the sensory system keep up with the ever-changing external world? As later discussed, 'prediction' and 'postdiction' are essential keywords here. For example, the sensory system uses temporally preceding events to predict subsequent events (e.g., Nijhawan, 1994; Kerzel, 2003; Hubbard, 2005) even when the preceding event is subliminally presented (Schmidt, 2000). Moreover, internal prediction modulates the perception of action outcomes (Bays et al., 2005; Cardoso-Leite et al., 2010) and sense of agency (Wenke et al., 2010). Prediction is also an indispensable factor for movement planning and control (Kawato, 1999). On the other hand, the sensory system also makes use of subsequent events to postdictively interpret a preceding event (e.g. Eagleman & Sejnowski, 2000; Enns, 2002; Khuu et al., 2010; Kawabe, 2011, 2012; Miyazaki et al., 2010; Ono & Kitazawa, 2011) and it's much the same even for infancy (Newman et al., 2008). Moreover, it has also been proposed that sense of agency stems not only from predictive processing but also from postdictive inference (Ebert & Wegner, 2011). The existence of postdictive processing is also supported by several neuroscience studies (Kamitani & Shimojo, 1999; Lau et al., 2007). How prediction and postdiction shape awareness of the external world is an intriguing question. Prediction is involved with the encoding of incoming signals, whereas postdiction is related to a re-interpretation of already encoded signals. Given this perspective, prediction and postdiction may exist along a processing stream for a single external event. However, it is unclear whether, and if so how, prediction and postdiction interact with each other to shape awareness of the external world. Awareness of the external world may also shape prediction and/or postdiction. It is plausible that awareness of the external world drives the prediction and postdiction of future and past appearances of the world. However, the literature provides little information about the role of awareness of the external world in prediction and postdiction. This background propelled us to propose this research topic with the aim of offering a space for systematic discussion concerning the relationship between awareness, prediction and postdiction among researchers in broad research areas, such as psychology, psychophysics, neuroscience, cognitive science, philosophy, and so forth. We encouraged papers that address one or more of the following questions: 1) How does prediction shape awareness of the external world? 2) How does postdiction shape awareness of the external world? 3) How do prediction and postdiction interact with each other in shaping awareness of the external world? 4) How does awareness of the external world shape prediction/postdiction?